2014
DOI: 10.1038/eye.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents retinal oxidative stress and vascular changes in diabetic rats

Abstract: Purpose To evaluate the role of melatonin, an antioxidant agent, in diabetic oxidative stress and vascular damage. Methods Diabetes was induced in 21 male Wistar rats by intraperitoneal (IP) administration of streptozotocin and then the rats were equally and randomly allocated to diabetic, melatonin, and vehicle groups. Seven healthy normal rats with similar features comprised the control group as the fourth group. All animals were followed for 12 weeks. The melatonin group received IP melatonin daily and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
3
40
0
1
Order By: Relevance
“…The dose of melatonin used (10 mg/kg/d) was selected based on previous studies. 36,37 Our results demonstrated that melatonin ameliorated lipid metabolism, hemodynamic and endothelial dysfunctions, and vascular hyperpermeability to a various extent in diabetic rats. Most importantly, our study is the first to show that the suppression of MLCK-and p-MYPT-mediated p-MLC expression, which was partly associated with the ERK/ p38 signal transduction pathway for the alleviation of hyperpermeability in both hyperglycemic and hypercholesterolemic states, played a crucial role in the protective effects of melatonin.…”
Section: Discussionmentioning
confidence: 90%
“…The dose of melatonin used (10 mg/kg/d) was selected based on previous studies. 36,37 Our results demonstrated that melatonin ameliorated lipid metabolism, hemodynamic and endothelial dysfunctions, and vascular hyperpermeability to a various extent in diabetic rats. Most importantly, our study is the first to show that the suppression of MLCK-and p-MYPT-mediated p-MLC expression, which was partly associated with the ERK/ p38 signal transduction pathway for the alleviation of hyperpermeability in both hyperglycemic and hypercholesterolemic states, played a crucial role in the protective effects of melatonin.…”
Section: Discussionmentioning
confidence: 90%
“…These are, but not limited to, the fact that melatonin suppresses the levels of TNF-a, IFN-a, IL6, IL8, TF, MCP-1, VEGF, phosphorylation of JNK, and the degradation of the tight junctional proteins and it reduces endothelial apoptosis [13][14][15] Protecting against endothelial cell injury and preserving vascular structure and function are important to avoid the deadly hemorrhage in late stage EVD.…”
Section: Melatonin and Its Potential Effects On Ebola Pathologymentioning
confidence: 99%
“…In this sense, melatonin can modulate sirtuins expression/activity and can induce autophagy via mTOR‐dependent pathway (Figure ) . Furthermore, some of the sirtuins effects described above have also been reported for melatonin . Indeed, melatonin treatment of diabetic rats inhibits their MMP‐9 expression and VEGF secretion (Figure ) .…”
Section: Melatonin and Aging‐related Eye Diseasesmentioning
confidence: 74%
“…Certainly, melatonin offers protection from oxidative stress and increases the viability of retinal cells involved in diabetic retinopathy including RPE, photoreceptors, retinal ganglion cells, and Müller cells (Figure ) . Furthermore, melatonin prevents the nitro‐oxidative stress of diabetic retina and high glucose‐induced inflammatory response of RPE as well as retinal endothelial cells (Figure )…”
Section: Melatonin and Aging‐related Eye Diseasesmentioning
confidence: 99%